2020
DOI: 10.24251/hicss.2020.579
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of Entrepreneurship Education

Abstract: This study explores a multi-dimensional model for measuring the effectiveness of entrepreneurship education. The proposed model was validated through an empirical study involving 298 college students who have participated in entrepreneurship courses in China. The research results show that the effectiveness of entrepreneurship education can be observed through the improvement of participants' entrepreneurial competencies, the reduction of their entrepreneurial barriers and the change of their entrepreneurial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The relationship between entrepreneurial intentions and education is complex. For example, entrepreneurship education may sometimes reduce entrepreneurial intentions when students realize the required commitment (Liu et al, 2020(Liu et al, , 2021b. In this study, time commitment seemed to be an important barrier for students who were further along in their academic work.…”
Section: Limitations Discussion and Practical Implicationsmentioning
confidence: 68%
“…The relationship between entrepreneurial intentions and education is complex. For example, entrepreneurship education may sometimes reduce entrepreneurial intentions when students realize the required commitment (Liu et al, 2020(Liu et al, , 2021b. In this study, time commitment seemed to be an important barrier for students who were further along in their academic work.…”
Section: Limitations Discussion and Practical Implicationsmentioning
confidence: 68%
“…Previous researchers provide conceptual differences between entrepreneurship education and the effectiveness of entrepreneurship education. Entrepreneurship education is explained by the scope of the study in a series of courses in the entrepreneurship program (Liu et al, 2020) for students to improve their competence. One form of education that aims to transform the public is entrepreneurship education, which must have an impact on students, and this positive impact of entrepreneurship is called the effectiveness of entrepreneurship education (Liu et al, 2020).…”
Section: B Literature Review 1 Entrepreneurship Educationmentioning
confidence: 99%
“…Entrepreneurship education is explained by the scope of the study in a series of courses in the entrepreneurship program (Liu et al, 2020) for students to improve their competence. One form of education that aims to transform the public is entrepreneurship education, which must have an impact on students, and this positive impact of entrepreneurship is called the effectiveness of entrepreneurship education (Liu et al, 2020). There are many perspectives in measuring the effectiveness of entrepreneurship education, including entrepreneurial competence, entrepreneurial barriers, and entrepreneurial intention (Liu et al, 2020) (Kriz & Auchter, 2016;Giacomin et al, 2011).…”
Section: B Literature Review 1 Entrepreneurship Educationmentioning
confidence: 99%
“…They found that the impact of entrepreneurship education can be quantified by "the improvement of participants' entrepreneurial competencies, the reduction of entrepreneurial barriers and the change of entrepreneurial intention" (p. 4712). Although research has not found entrepreneurial education to have a significant impact on future entrepreneurial success (Bae et al, 2014), Liu et al's (2020) results may encourage future research to learn from and improve entrepreneurial education to increase its impact on future entrepreneurs.…”
Section: Challengesmentioning
confidence: 93%
“…Although prior knowledge does not seem to play a role in future success (Davidsson & Honig, 2003), prior experience with entrepreneurial endeavors does impact "entrepreneurial characteristics, behavior and intention" (Ramayah et al, 2012, p. 65). Liu et al (2020) conducted a study to find how to measure the impact of education in entrepreneurship. They found that the impact of entrepreneurship education can be quantified by "the improvement of participants' entrepreneurial competencies, the reduction of entrepreneurial barriers and the change of entrepreneurial intention" (p. 4712).…”
Section: Challengesmentioning
confidence: 99%